2009
DOI: 10.2460/ajvr.70.6.758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a tart cherry juice blend on exercise-induced muscle damage in horses

Abstract: Administration of TCJB may diminish muscle damage induced by exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…For the purpose of statistical analysis, all samples with a result below the limit of detection were assigned a value of 20 pg/ml. Thiobarbituric acid reactive substances (TBARS) were measured fluorometrically using a commercial kit previously validated in the horse (Ducharme et al . 2009) 3 .…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of statistical analysis, all samples with a result below the limit of detection were assigned a value of 20 pg/ml. Thiobarbituric acid reactive substances (TBARS) were measured fluorometrically using a commercial kit previously validated in the horse (Ducharme et al . 2009) 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Besides concerns regarding the possibility that excessive use of NSAIDS may contribute to race-related injuries [33], long-term use of NSAIDs is associated with other adverse effects [35]. Thus, there is growing interest in nonpharmacologic approaches to ameliorate exercise-induced inflammation [36][37][38][39]. Various dietary supplements have been proposed to alleviate exercise-related injuries and illnesses [40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, measuring the serum SAA concentration before entering a competition may indicate whether the horse is in poor condition, including subclinical disorders, overtraining or slight injuries that may worsen with exertion and lead to elimination from the ride [25]. Other authors have reported an increase in SAA concentration after moderate treadmill exercise during an experimental study on the effect of an antioxidative compound on exercise-induced muscle damage [27]. This observation is in agreement with Liburt’s et al findings that the level of proinflammatory and acute phase-related cytokines, including IL-1, TNF-α and IL-6 (in the muscles), increased after an incremental exercise test in unfit Standardbreds [28].…”
Section: Introductionmentioning
confidence: 99%